A multicenter cross-sectional study to evaluate the clinical characteristics and nutritional status of children with cerebral palsy - Aydin, Kursad; Akbas, Yilmaz; Unay, Bulent; Arslan, Mutluay; Cansu, Ali; Sahin, Sevim; Sarioglu, Aysugul Alptekin (Elsevier Ltd, 2018)
Background & aims: This study was designed to assess clinical characteristics and nutritional status of pediatric outpatients with cerebral palsy (CP) and to determine prevalence of malnutrition based on physicians’ clinical judgment and on anthropometric data in relation to percentile reference values. Methods: A total of 1108 pediatric neurology outpatients (mean ± SEM age: 7.2 ± 0.1 years, 59.3% were males) diagnosed with CP were included in this cross-sectional, non-interventional multicenter single-visit study conducted between October 2015 and July 2016 at 20 centers across Turkey. Data on patient and CP characteristics, concomitant nonneuromotor impairments and gastrointestinal disorders as well as anthropometrics, outcome of nutritional status assessment (via physicians’ clinical judgment and Gomez classification and Waterlow classification of anthropometric data) and physician's view on nutritional care in CP patients were collected at a single visit. Results: The most common CP etiology was asphyxia (62.5%). The most common clinical category was spastic CP (87.5%) with quadriplegic (54.0%) topography and level V gross motor dysfunction (45.4%) in most of patients. The prevalence of malnutrition was considered to be 57.2% based on physicians’ clinical judgment, while shown to be 94.3% (3rd degree in 86.7%) according to Gomez classification of Neyzi weight for age (WFA) percentiles and to be 91.3% (severe in 88.3%) according to Waterlow classification of Neyzi height for age (HFA) percentiles. Conclusions: In conclusion, our findings revealed high prevalence of malnutrition, while also emphasize the likelihood of overestimation of malnutrition in children with CP when anthropometric assessment was based on use of growth charts for general pediatric population. This large-scale survey provided valuable data regarding nutritional assessment practice and malnutrition prevalence among children with CP in Turkey, which may be utilized for future proactive strategies in the prevention and treatment of malnutrition in this population. © 2018 European Society for Clinical Nutrition and Metabolism
Keywords: Anthropometrics; Cerebral palsy; Growth charts; Malnutrition; Pediatric outpatients